Age- and gender-related changes in glucose homeostasis in glucocorticoid-treated rats - Santos, Cristiane dos; Ferreira, Francielle Batista D.; Goncalves-Neto, Luiz M.; Taboga, Sebastiao Roberto [UNESP]; Boschero, Antonio Carlos; Rafacho, Alex (Canadian Science Publishing, Nrc Research Press, 2014)
The disruption to glucose homeostasis upon glucocorticoid (GC) treatment in adult male rats has not been fully characterized in older rats or in females. Thus, we evaluated the age-and gender-related changes in glucose homeostasis in GC-treated rats. We injected male and female rats at 3 months and 12 months of age with either dexamethasone (1.0 mg/kg body mass, intraperitoneally) or saline, daily for 5 days. All of the GC-treated rats had decreased body mass and food intake, and adrenal hypotrophy. Increased glycemia was observed in all of the GC-treated groups and only the 3-month-old female rats were not glucose intolerant. Dexamethasone treatment resulted in hyperinsulinemia and hypertriacylglyceridemia in all of the GC-treated rats. The glucose-stimulated insulin secretion (GSIS) was higher in all of the dexamethasone-treated animals, but it was less pronounced in the older animals. The beta-cell mass was increased in the younger male rats treated with dexamethasone. We conclude that dexamethasone treatment induces glucose intolerance in both the 3- and 12-month-old male rats as well as hyperinsulinemia and augmented GSIS. Three-month-old female rats are protected from glucose intolerance caused by GC, whereas 12-month-old female rats developed the same complications that were present in 3- and 12-month-old male rats.
Keywords: dexamethasone; female; glucose tolerance; insulin secretion; insulin sensitivity